Respuesta :

slope = [tex]\frac{1}{12}[/tex]

the slope is the value of f' (36)

f(x) = √x = [tex]x^{\frac{1}{2} }[/tex]

f'(x) = [tex]\frac{1}{2}[/tex] [tex]x^{-\frac{1}{2} }[/tex] = [tex]\frac{1}{2\sqrt{x} }[/tex]

f'(36) = [tex]\frac{1}{2(6)}[/tex] = [tex]\frac{1}{12}[/tex]


Answer:

[tex]slope = \frac{1}{12}[/tex]

Step-by-step explanation:

Here is another method to solve your problem. I am showing this method because this is the first method normally taught and a student might not of had the chance yet to learn the other methods


We can solve this problem by using limits and the following function

[tex]\lim_{h\to 0} \frac{f(x+h) - x}{h}[/tex]

[tex]\lim_{h\to 0} \frac{\sqrt{x+h} - \sqrt{x}}{h}[/tex]

Next multiply by the conjugate of the numerator.

[tex]\lim_{h\to 0} \frac{\sqrt{x+h} - \sqrt{x}}{h} * \frac{\sqrt{x+h} + \sqrt{x}}{\sqrt{x+h} + \sqrt{x}}[/tex]

[tex]\lim_{h\to 0} \frac{x + h - x}{h(\sqrt{x+h} + \sqrt{x})}[/tex]

Cancel the x - x

[tex]\lim_{h\to 0} \frac{h}{h(\sqrt{x+h} + \sqrt{x})}[/tex]

Divide out the h

[tex]\lim_{h\to 0} \frac{h}{h(\sqrt{x+h} + \sqrt{x})}[/tex]

[tex]\lim_{h\to 0} \frac{1}{(\sqrt{x+h} + \sqrt{x})}[/tex]

Plugin 0 where h is located

[tex]\lim_{h\to 0} \frac{1}{(\sqrt{x+h} + \sqrt{x})}[/tex]

[tex]\lim_{h\to 0} \frac{1}{(\sqrt{x+0} + \sqrt{x})}[/tex]

[tex]\lim_{h\to 0} \frac{1}{(\sqrt{x} + \sqrt{x})}[/tex]

Combine Like terms in denominator

[tex]\lim_{h\to 0} \frac{1}{(\sqrt{x} + \sqrt{x})}[/tex]

[tex]\lim_{h\to 0} \frac{1}{2\sqrt{x}}[/tex]

Now lets use our derivative and plugin 36 where x is located and solve

[tex]\frac{1}{2\sqrt{x}}[/tex]

[tex]\frac{1}{2\sqrt{36}}[/tex]

[tex]\frac{1}{2(6)}[/tex]

[tex]\frac{1}{12}[/tex]


Note, this is a harder method but it is normally the first method taught in Calculus 1.